Preparation method of covalent organic polymer thin-layer composite membrane based on boroxane and diol amine dual cross-linked network
Through the double cross-linked network structure based on hexaborane and diolamine, the stability and selectivity problems of covalent organic polymer thin layer composite membranes were solved, and high-performance membrane material applications were achieved, especially in the separation of dye wastewater in water treatment.
Patent Information
- Application Number
- CN202510878287.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-27
- Publication Date
- 2025-10-03
AI Technical Summary
Existing technologies make it difficult to prepare high-performance, stable covalent organic polymer thin-layer composite membranes. Traditional methods have problems such as nanofiller incompatibility, leaching, and structural instability, especially in nanofiltration applications, which require high costs and time.
A double cross-linked network structure based on hexaboron oxide and diolamine was adopted. The organic boron compound BPBA was prepared by pretreating the commercial PVDF ultrafiltration membrane, and a cross-linked network of hexaboron oxide and diolamine was formed under vacuum and heating conditions to construct a double cross-linked network coating.
The chemical stability and thermal stability of the composite membrane are significantly improved, and it has excellent hydrophilicity and selectivity, which increases the dye retention rate and is suitable for dye wastewater separation applications in the water treatment field.
Smart Images

Figure CN120733580A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of organic polymer composite membranes, in particular to a method for preparing a covalent organic polymer thin-layer composite membrane based on a double cross-linked network of hexaborane and diolamine. Background Art
[0002] Covalent organic polymers (COPs) are polymerized from small organic molecule monomers and are porous materials with a highly cross-linked network structure connected by covalent bonds. They have a series of advantages such as high surface area, integrated adsorption sites, flexibility, insolubility, low density, high thermal stability and chemical stability. In recent studies, COPs have been widely used and classified into covalent organic frameworks (COFs), intrinsically microporous polymers (PIMs), conjugated micro / mesoporous polymers (CMPs) and hyper-cross-linked polymers (HCPs).
[0003] Covalent organic polymers (COPs) are considered promising membrane materials, but growing COPs into a continuous porous skin is challenging. The structural joints should be sufficiently reactive and flexible or semi-rigid to produce a continuous porous skin layer. In sharp contrast to crystalline COFs with long-range ordered pores, amorphous or semi-crystalline COPs usually exhibit disordered pores with a relatively narrow size distribution. However, unlike the synthesis of highly crystalline COFs, COPs are usually synthesized via simple procedures and mild conditions with short reaction times. More importantly, the strong covalent bonds in COPs can prevent the framework structure from distorting, resulting in pores with a relatively narrow size distribution. These unique properties of COPs may allow rapid solvent penetration without significantly reducing selectivity.
[0004] Despite the broad application prospects of COPs in membrane materials, their growth into a continuous porous surface layer remains challenging. Traditional preparation methods have numerous shortcomings. For example, incorporating COPs as fillers into polymer matrices to prepare mixed matrix membranes (MMMs) is relatively simple, but the favorable intrinsic transport properties of the nanofiller may be degraded or nearly lost due to the permeability of the matrix. Leaching, agglomeration, and incompatibility with the polymer matrix may also present challenges. Furthermore, the most common synthesis method for crystalline COPs and their derivatives is the boronic acid condensation reaction. However, the electron-deficient boron sites of the borane covalent organic framework (COF) are susceptible to nucleophilic attack by water. Even in slightly humid air, the integrity of the porous framework can be destroyed within hours. This instability is a major limitation to the application of borane hexacyclic COFs. Furthermore, the application of COP membranes in nanofiltration requires extended times and higher temperatures, which undoubtedly increases the cost and difficulty of preparation. Therefore, traditional techniques have significant drawbacks in preparing high-performance, stable COPs thin-layer composite membranes and cannot meet the requirements of practical applications. Summary of the Invention
[0005] The present invention aims to overcome the deficiencies of the prior art and provides a method for preparing a covalent organic polymer thin-layer composite membrane based on a double cross-linked network of hexaborane and diolamine. The method comprises pre-treating a commercial PVDF ultrafiltration membrane to remove surface impurities, preparing an organic boron compound BPBA, causing the epoxy groups on the GTE molecular chain to undergo a nucleophilic ring-opening reaction with the amino groups of APBA through a specific reaction, then blending BPBA solutions of varying concentrations with a glyoxal solution, and immersing the pre-treated base membrane in a casting solution. Finally, under vacuum and heating conditions, the phenylboronic acid groups on the membrane surface undergo dehydration condensation to form a hexaborane cross-linked network, while glyoxal reacts with amines to form a diolamine cross-linked network, thereby constructing a double cross-linked network coating. The resulting composite membrane adopts a double cross-linked network structure, significantly improving chemical and thermal stability, and solving the problem of the traditional hexaborane structure being susceptible to water attack. The membrane also exhibits excellent hydrophilicity, selectivity, and separation performance, with a high dye retention rate. The membrane has broad application prospects in the field of water treatment, especially in the separation of dye wastewater.
[0006] In order to solve the above technical problems, the present invention provides the following technical solution: a method for preparing a covalent organic polymer thin layer composite membrane based on a double cross-linked network of hexaborane and diolamine, the method comprising the following specific steps: Base membrane pretreatment: The commercial PVDF ultrafiltration membrane was ultrasonically cleaned with deionized water and then air-dried at room temperature for use; Preparation of the organic boron compound BPBA: 3-aminophenylboronic acid and propylene glycol triglycidyl ether were dissolved in DMF, and the purified BPBA product was obtained by rotary evaporation. Anhydrous ethanol solution was added to prepare the BPBA casting solution; Casting solution preparation and base membrane impregnation: After mixing BPBA solutions of different concentrations with glyoxal solution, the pretreated PVDF base membrane was immersed in it and allowed to stand; Double cross-linking membrane formation and post-treatment: The impregnated base membrane was cross-linked in a vacuum oven at 100°C for 1 hour, washed with ethanol and deionized water to obtain a PVDF@BPBAx-Gy composite membrane.
[0007] Furthermore, in the preparation step of the organoboron compound BPBA, 3-aminophenylboronic acid APBA and glycerol triglycidyl ether GTE are completely dissolved in 8 ml of N,N-dimethylformamide DMF in a certain proportion, and the molar ratio of APBA to GTE is 3:1. The reaction solution is placed in an oil bath at 90°C and stirred for reaction for 12 hours. During the reaction, the epoxy group on the GTE molecular chain undergoes a nucleophilic ring-opening reaction with the amino group of APBA, thereby generating a trifunctional phenylboronic acid compound BPBA, ensuring the structural integrity and reaction conversion rate of BPBA.
[0008] Furthermore, in the preparation step of the organoboron compound BPBA, 30 ml of anhydrous ethanol solution is added to the purified BPBA product. The concentration of the BPBA solution is measured by drying 1 ml of the solution in a vacuum oven at 90°C for 12 hours to remove the solvent, providing accurate data for subsequent casting solution concentration control.
[0009] Furthermore, in the casting liquid preparation and base film impregnation steps, BPBA solutions of different concentrations and glyoxal solutions of different concentrations are mixed at room temperature for 90 seconds to form a casting liquid, and the pretreated PVDF base film is immersed in the casting liquid and allowed to stand for 90 seconds to allow the casting liquid to evenly adhere to the surface of the base film. The casting liquid is evenly adhered to the surface of the base film through capillary action to ensure uniform film formation.
[0010] Furthermore, the concentration of the BPBA solution is 0.8-2.4wt%, and the concentration of the glyoxal solution is 0.8-2.4wt%. Within this concentration range, the prepared composite membrane has a dye retention rate of up to 99.1% and a water flux of 65LMHB, taking into account both permeability and separation performance.
[0011] Furthermore, in the double cross-linking film-forming and post-treatment steps, the impregnated base film is placed in a vacuum oven at 100°C for 1 hour. Under vacuum and heating conditions, the phenylboronic acid groups in BPBA on the surface of the base film are dehydrated and condensed to form a hexacyclic borane-oxygen cross-linked network. At the same time, glyoxal and amine undergo aminolysis reaction to form a diolamine cross-linked network, constructing a double cross-linked network coating. The synergistic effect of the double network improves the thermal stability of the composite membrane, and the structure remains stable at 426°C.
[0012] Furthermore, in the double cross-linking film-forming and post-processing steps, the cross-linking conditions of the vacuum oven are 100°C, vacuum degree ≤0.08MPa, and processing time 1 hour. Under these conditions, the dehydration condensation efficiency of the phenylboronic acid group is high, while avoiding excessive volatilization of glyoxal, ensuring the complete construction of the double cross-linking network.
[0013] Furthermore, in the double cross-linking film formation and post-treatment steps, after film formation, the composite membrane is immersed in ethanol for 30 minutes to remove residual compounds, and then washed with deionized water to remove residual ethanol, and washed until neutral to obtain a covalent organic polymer thin layer composite membrane, named PVDF@BPBAx-Gy membrane, where x is the BPBA concentration and y is the glyoxal concentration. The surface B element content is 0.8-1.5at%, the membrane surface roughness Ra is reduced to 40.3±0.9nm, and the hydrophilicity is significantly improved.
[0014] Compared with the existing technology, the preparation method of the covalent organic polymer thin layer composite membrane based on the double cross-linked network of hexaborane and diolamine has the following beneficial effects: 1. The present invention greatly improves the stability of the composite membrane by adopting a double cross-linked network structure based on hexaborane and diolamine. In the double cross-linked network, the hexaborane cross-linked network and the diolamine cross-linked network cooperate with each other to form a stable framework structure. The diolamine cross-linked network enhances the chemical bonding strength of the membrane, effectively blocks the invasion of water molecules, and prevents the hexaborane structure from being destroyed. At the same time, this double cross-linked structure also improves the thermal stability of the membrane, so that it can still maintain the integrity of the structure at higher temperatures, and is not prone to deformation or decomposition, providing reliable protection for the membrane in complex and changeable practical application environments. 2. The composite membrane prepared by the present invention performs excellent in separation performance, and the preparation process is suitable for large-scale production. In terms of separation performance, the composite membrane obtained has excellent hydrophilicity, which is conducive to the rapid passage of water molecules. At the same time, it has a high selective interception ability for dye molecules and can also ensure good permeability to inorganic salts.
[0015] Other advantages, objects and features of the present invention will be described in part in the following description and, in part, will be apparent to those skilled in the art based on an examination of the following or may be learned from the practice of the invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for the embodiments or the description of the prior art. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative work. Figure 1 Flowchart for the synthesis of covalent organic polymers with dual cross-linked networks; Figure 2 NMR of covalent organic polymers with double cross-linked networks ( 1 HNMR) and infrared (FT-IR) spectra; Figure 3 Thermogravimetric (TGA) curve and stability diagram of the covalent organic polymer with a double cross-linked network; Figure 4 The figure shows the preparation process of covalent organic polymer thin layer composite membrane; Figure 5 High-resolution fitting curve diagram and element content table of B1s spectrum of covalent organic polymer thin layer composite film; Figure 6 Surface SEM, cross-sectional SEM and AFM images of the covalent organic polymer thin layer composite film and the original film; Figure 7The static water contact angle diagram (at 20°C) and Zeta potential diagram of the covalent organic polymer thin layer composite film and the original film; Figure 8 The water flux diagram of the covalent organic polymer thin layer composite membrane and the original membrane, and the MWCO curve and pore size distribution diagram of filtering PEG solutions with different molecular weights; Figure 9 The figure shows the permeation flux and retention performance of covalent organic polymer thin layer composite membrane in filtering dyes with different molecular weights; Figure 10 The permeation flux and retention performance diagram of covalent organic polymer thin layer composite membrane filtering different inorganic salt solutions; Figure 11 Composite membrane PVDF @ BPBA 1.6 -G 0.8 Mechanism diagram, permeation flux and retention performance diagram of filtration of CR and mixed solutions of different inorganic salts; Figure 12 Composite membrane PVDF @ BPBA 1.6 -G 0.8 Spectra of UV absorbance of mixed dyes with different molecular weights; Figure 13 Composite membrane PVDF @ BPBA 1.6 -G 0.8 Long-term stability diagram of separated CR / NaCI mixed solution. DETAILED DESCRIPTION
[0017] In order to further illustrate the technical means and effects adopted by the present invention to achieve the predetermined purpose of the invention, the specific implementation methods, structures, features and effects of the present invention are described in detail below in conjunction with the accompanying drawings and preferred embodiments.
[0018] The invention provides a preparation method of a covalent organic polymer thin-layer composite membrane based on a double cross-linked network of hexaborane and diolamine. The method comprises the following steps: pre-treating a commercial PVDF ultrafiltration membrane to remove surface impurities; preparing an organic boron compound BPBA; causing the epoxy groups on the GTE molecular chain to undergo a nucleophilic ring-opening reaction with the amino groups of APBA through a specific reaction; then blending BPBA solutions of different concentrations with a glyoxal solution; and immersing the pre-treated base membrane in a casting solution. Finally, under vacuum and heating conditions, the phenylboronic acid groups on the membrane surface are dehydrated and condensed to form a hexaborane cross-linked network, while glyoxal and amines undergo an aminolysis reaction to form a diolamine cross-linked network, thereby constructing a double cross-linked network coating. The prepared composite membrane adopts a double cross-linked network structure, significantly improves chemical stability and thermal stability, solves the problem that the traditional hexaborane structure is susceptible to water attack, and has excellent hydrophilicity, selectivity and separation performance, and a high dye retention rate. The method has broad application prospects in the field of water treatment, especially in the separation of dye wastewater.
[0019] Example 1: 4.11 g (30 mmol) of 3-aminophenylboronic acid (APBA) and 2.61 g (10 mmol) of glycerol triglycidyl ether (GTE) were added to a 50 ml round-bottom flask, and 8 ml of N,N-dimethylformamide (DMF) was slowly poured into it. The mixture was stirred at room temperature for 30 minutes using a magnetic stirrer until it was completely dissolved, forming a clear and transparent light yellow solution (such as Figure 1 (as shown in (A)).
[0020] The chemical formula of the 3-aminophenylboronic acid is as follows: ;
[0021] The chemical formula of the glycerol triglycidyl ether is as follows: ;
[0022] The round-bottom flask was placed in a 90°C oil bath, equipped with a condensing reflux device, and stirred at 200 rpm for 12 hours. The solution gradually turned light brown in the early stage of the reaction and reddish brown in the later stage. During this period, the epoxy groups on the GTE molecular chain reacted with the amino groups of APBA to produce a trifunctional phenylboronic acid compound BPBA (reaction mechanism as shown in the following figure). Figure 1 (as shown in the "Primary crosslinking" step in the .
[0023] The chemical formula of the trifunctional phenylboronic acid compound BPBA is shown below: ;
[0024] After the reaction, the solution was transferred to a rotary evaporator and the residual DMF was removed by rotary evaporation at 60°C and a vacuum degree of ≤0.08 MPa to obtain a reddish-brown viscous solid product. 30 ml of anhydrous ethanol was added to the product and ultrasonically vibrated for 15 minutes to completely dissolve it to prepare a BPBA casting solution. 1 ml of the solution was placed in a constant-weight culture dish and dried in a vacuum oven at 90°C for 12 hours. The concentration of the BPBA solution was determined to be 303.16 mg / ml by weighing the residual solid mass (the concentration determination principle is as follows). Figure 3 As shown in the TGA curve, the weight loss from 50 to 283 °C is attributed to the adsorption of water and dehydration condensation of boric acid.
[0025] Example 2: Take a commercial PVDF ultrafiltration membrane (effective area 10 cm × 10 cm), put it into 500 ml of deionized water, and clean it in an ultrasonic cleaner with a power of 300 W and a frequency of 40 kHz for 20 minutes to remove surface impurities. After taking it out, spread it flat on clean filter paper and air-dry it at room temperature (25℃±2℃) for 2 hours before use (the original morphology of the basement membrane is as follows Figure 6As shown in the SEM image of A1 in the middle, a macroporous structure is visible on the surface).
[0026] Casting solution preparation: Prepare a 1.6 wt% BPBA solution: Take 5.0 ml of 303.16 mg / ml BPBA ethanol solution, dilute with 95 ml of anhydrous ethanol, and stir well. Prepare 0.8 wt% glyoxal solution: weigh 0.8 g of glyoxal (mass fraction 40%), add 99.2 ml of deionized water to dissolve, and stir evenly.
[0027] The chemical formula of glyoxal is shown in the figure below: ;
[0028] The above two solutions were mixed in a 50 ml beaker at a volume ratio of 1:1 and stirred at a constant speed for 90 seconds using a glass rod to form a uniform and transparent casting solution (the solution blending state is as follows Figure 1 (as shown in (B)).
[0029] The pretreated PVDF base membrane was immersed horizontally in the casting solution and allowed to stand for 90 seconds to allow the membrane surface to evenly absorb the casting solution. After taking it out, excess liquid on the edge was absorbed with filter paper and immediately placed in a vacuum oven preheated to 100°C (vacuum degree ≤ 0.08MPa) for 1 hour of cross-linking treatment. During this process, the phenylboronic acid groups in BPBA dehydrated and condensed to form a hexacyclic boron oxide cross-linking network, and glyoxal reacted with amine substances to form a diolamine cross-linking network, thus constructing a double cross-linked coating on the membrane surface (cross-linking process as shown in Figure 2). Figure 4 Boroxineand Diamine network shown in ).
[0030] After cross-linking, the membrane was immersed in 100 ml of anhydrous ethanol for 30 minutes to remove unreacted monomers and by-products, and then rinsed repeatedly with deionized water for 3 times, 5 minutes each time, until the pH value of the washing solution reached 7. The final composite membrane was named PVDF@BPBA X -Gy, the chemical state of the surface B element is as follows Figure 5 As shown in the B1s spectrum, characteristic peaks such as B3O3 (194.5eV) and OBO (192.8eV) were detected, confirming the existence of the hexacyclic boron oxide.
[0031] Example 3: The prepared BPBA solid sample was dissolved in deuterated dimethyl sulfoxide (DMSO-d6) and tested on a 400MHz nuclear magnetic resonance spectrometer. The results showed that the characteristic peak of -NH2 at 4.6-5.2ppm in APBA disappeared, and the signal peaks of -OH (j) at 4.6-5ppm and -NH (i) at 8-8.6ppm appeared. The peak area of the characteristic peak of the benzene ring (a) (6.4-7ppm) was twice that of the -OH and -NH peak areas, confirming the synthesis of BPBA (the spectrum is shown in FIG. Figure 2 shown by the red line).
[0032] The prepared PVDF@BPBA 1.6 -G 0.8 The membrane was cut into pieces, mixed with KBr and pressed into pellets, and then tested on a Fourier transform infrared spectrometer. The results showed that the 1636 cm −1 The C=O characteristic peak of glyoxal disappears and the peak at 1255 cm −1 and 1092cm −1 The CO / COC stretching vibration peak at 790 cm-1 and the B3O3 characteristic peaks at 706 cm-1 confirmed the formation of a double cross-linked network (the spectrum is shown in Figure 2). Figure 2 shown by the middle blue line).
[0033] SEM observation: PVDF@BPBA 1.6 -G 0.8 The membrane samples were gold-sprayed and the surface and cross-sectional morphologies were observed under a scanning electron microscope. The surface SEM images showed that a dense cross-linked network was formed on the membrane surface, with no obvious macroporous structure (such as Figure 6 As shown in B3 in the figure, the cross-sectional SEM image shows that the coating thickness is uniform and about 157.8 nm (as shown in Figure 6 (as shown in C3 in the figure).
[0034] AFM test: Atomic force microscope was used to scan the membrane surface in tapping mode to measure the PVDF@BPBA 1.6 -G 0.8 The surface roughness Ra of the membrane is 40.3±0.9nm, which is about 1 / 2 of the original PVDF membrane (Ra=75.1±4.2nm) (e.g. Figure 6 (as indicated by A3 in the figure).
[0035] Water contact angle measurement: At 20°C, 5 μL of deionized water was added to the membrane surface using a contact angle meter to measure the PVDF@BPBA 1.6 -G 0.8 The water contact angle of the membrane is 46.50±0.95°, which is lower than the 62.4±1.5° of the original PVDF membrane (test results are shown in Figure 7 left).
[0036] Zeta potential test: The membrane sample was made into a 1 cm diameter disc, and the streaming potential was measured with 1 mM KCl solution in the pH range of 3-9. The results showed that PVDF@BPBA 1.6 -G 0.8 The membrane surface is negatively charged, and the zeta potential value is slightly higher than that of the original PVDF membrane (e.g. Figure 7 (as shown in the figure on the right).
[0037] Water flux measurement: The membrane permeability was tested using deionized water at an operating pressure of 0.1 MPa. 1.6 -G 0.8 The pure water flux of the membrane is 75LMHB, which is lower than the 650LMHB of the original PVDF membrane, indicating that the membrane pore size is reduced due to the construction of the cross-linked network (flux data are shown in Figure 8 shown).
[0038] Dye retention experiment: Using 50 mg / L crystal violet (CR, Mw=696.7 g / mol) solution as the feed liquid, the retention rate was tested at a pressure of 0.1 MPa, PVDF @ BPBA 1.6 -G 0.8 The membrane's rejection rate for CR was 99.1%, and the permeation flux was 65LMHB (the results are shown in Figure 9 (as shown by the C1 curve in the figure).
[0039] Inorganic salt separation experiment: When filtering 1g / L NaCl solution, PVDF @ BPBA 1.6 -G 0.8 The rejection rate of the membrane is only about 5%, while the rejection rate of Na2SO4 is slightly higher (such as Figure 10 ), showing the selectivity for different inorganic salts.
[0040] Mixed solution separation: When filtering CR / NaCl mixed solution, the membrane has a CR rejection rate of 99.4%, a NaCl rejection rate of 14%, and a separation coefficient of 143.3 (e.g. Figure 11 (B and C in the figure) confirm the synergistic effect of size screening and electrostatic repulsion.
[0041] Mixed dye separation: UV-visible spectrometer was used to detect the separation effect of the membrane on mixed dyes (MO+MB). The results showed that MB (596nm) was almost completely intercepted, while MO (466nm) was partially transmitted (e.g. Figure 12 As shown in A in the figure, it shows the screening ability of dyes with different molecular weights.
[0042] Long-term stability test: After continuous filtration of CR / NaCl mixed solution for 24 hours, the CR retention rate decreased from 99.4% to 95%, and the NaCl retention rate decreased from 19% to 4.76%, indicating that the membrane has good operational stability (such as Figure 13 shown).
[0043] The above description is merely a preferred embodiment of the present invention and does not constitute any form of limitation to the present invention. Although the present invention has been disclosed as above in terms of a preferred embodiment, it is not intended to limit the present invention. Any person skilled in the art can, without departing from the scope of the technical solution of the present invention, make some changes or modifications to equivalent embodiments using the technical contents disclosed above. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.
Claims
1. A method for preparing a covalent organic polymer thin layer composite membrane based on a double cross-linked network of hexaborane and diolamine, characterized in that: The method comprises the following specific steps: Base membrane pretreatment: The commercial PVDF ultrafiltration membrane was ultrasonically cleaned with deionized water and then air-dried at room temperature for use; Preparation of the organic boron compound BPBA: 3-aminophenylboronic acid and propylene glycol triglycidyl ether were dissolved in DMF and heated for reaction, and then purified by rotary evaporation to obtain the purified BPBA product, and anhydrous ethanol solution was added to prepare the BPBA casting solution; Casting solution preparation and base membrane impregnation: After mixing BPBA solutions of different concentrations with glyoxal solution, the pretreated PVDF base membrane was immersed in it and allowed to stand; Double cross-linking membrane formation and post-treatment: The impregnated base membrane was cross-linked in a vacuum oven at 100°C for 1 hour, washed with ethanol and deionized water to obtain a PVDF@BPBAx-Gy composite membrane.
2. The method for preparing a covalent organic polymer thin layer composite membrane based on a double cross-linked network of hexaborane and diolamine according to claim 1, characterized in that: In the preparation step of the organoboron compound BPBA, 3-aminophenylboronic acid APBA and glycerol triglycidyl ether GTE are completely dissolved in 8 ml of N,N-dimethylformamide (DMF) in a certain proportion, with a molar ratio of APBA to GTE of 3:
1. The reaction solution is placed in an oil bath at 90°C and stirred for 12 hours. During the reaction, the epoxy groups on the GTE molecular chain undergo a nucleophilic ring-opening reaction with the amino groups of APBA, thereby generating the trifunctional phenylboronic acid compound BPBA.
3. The method for preparing a covalent organic polymer thin layer composite membrane based on a double cross-linked network of hexaborane and diolamine according to claim 1, characterized in that: In the preparation step of the organoboron compound BPBA, 30 ml of anhydrous ethanol solution is added to the purified BPBA product, and the concentration of the BPBA solution is determined by drying 1 ml of the solution in a vacuum oven at 90° C. for 12 hours to remove the solvent.
4. The method for preparing a covalent organic polymer thin layer composite membrane based on a double cross-linked network of hexaborane and diolamine according to claim 1, characterized in that: In the casting solution preparation and base membrane impregnation steps, BPBA solutions of different concentrations and glyoxal solutions of different concentrations are mixed at room temperature for 90 seconds to form a casting solution, and the pretreated PVDF base membrane is immersed in the casting solution and allowed to stand for 90 seconds to allow the casting solution to evenly adhere to the surface of the base membrane.
5. The method for preparing a covalent organic polymer thin layer composite membrane based on a double cross-linked network of hexaborane and diolamine according to claim 4, characterized in that: The concentration of the BPBA solution is 0.8-2.4 wt %, and the concentration of the glyoxal solution is 0.8-2.4 wt %.
6. The method for preparing a covalent organic polymer thin layer composite membrane based on a double cross-linked network of hexaborane and diolamine according to claim 1, characterized in that: In the double cross-linking film-forming and post-treatment steps, the impregnated base film is placed in a vacuum oven at 100°C for 1 hour. Under vacuum and heating conditions, the phenylboronic acid groups in the BPBA on the surface of the base film are dehydrated and condensed to form a hexacyclic boron oxide cross-linked network, and at the same time, glyoxal undergoes an aminolysis reaction to form a diolamine cross-linked network, thereby constructing a double cross-linked network coating.
7. The method for preparing a covalent organic polymer thin layer composite membrane based on a double cross-linked network of hexaborane and diolamine according to claim 1, characterized in that: In the double cross-linking film-forming and post-processing steps, the cross-linking conditions of the vacuum oven are 100° C., vacuum degree ≤ 0.08 MPa, and processing time 1 hour.
8. The method for preparing a covalent organic polymer thin layer composite membrane based on a double cross-linked network of hexaborane and diolamine according to claim 1, characterized in that: In the double cross-linking film formation and post-treatment steps, after film formation, the composite membrane is immersed in ethanol for 30 minutes to remove residual compounds, and then washed with deionized water to remove residual ethanol and washed until neutral to obtain a covalent organic polymer thin layer composite membrane, named PVDF@BPBAx-Gy membrane, where x is the BPBA concentration and y is the glyoxal concentration.